Analisis Perhitungan Biaya Satuan (Unit Cost) Di STIE Port Numbay Tahun 2018 - Helmi Toatubun; Margo Saptowinarko Prasetyo (Musamus University, Merauke Papua Indonesia., 2020)
This study aims to find out and analyze how much the unit cost of providing education with the use of the ABC model at STIE Port Numbay in 2018. The research approach is qualitative and quantitative. Data analysis techniques in this study with the ABC system through two stages of activity namely the stage of identifying and determining the costs in the cost pool that has a similar activity and the stage of tracking and charging activity costs to each activity that gives attention to the cost driver. Based on the results of the analysis shows that the magnitude of the cost of implementing education units with the ABC model at STIE Port Numbay is Rp 4,930,610 every student every year while Rp 2,465,305 every semester. So the cost of providing education that has been set by STIE Port Numbay has been right. Keywords : Unit Cost, ABC Model.